Modification of the histone landscape with JAK inhibition in myeloproliferative neoplasms - Greenfield, G; McPherson, S; Smith, J; Mead, A; Harrison, C; Mills, K; McMullin, MF (MDPI, 2020)
Dysregulation of epigenetic processes is increasingly understood to play a role in the pathogenesis of myeloproliferative neoplasms (MPNs). Ruxolitinib, a JAK/STAT inhibitor, has proved a useful addition to the therapeutic arsenal for these disorders, but has limited disease modifying activity. We determined the effect of JAK inhibition on the histone landscape of MPN cells in cell line models of MPNs and validated using samples from the MAJIC randomised clinical trial of ruxolitinib in polycythaemia vera and essential thrombocythaemia. We demonstrated an epigenetic modifying effect of ruxolitinib using a histone modification assay. The majority of 21 histone H3 modifications were upregulated, with H3K27me3 and H3K36me2 significant in the combined cell line results. Chromatin immunoprecipitation and sequencing (CHIP-seq) for three marks of interest, H3K4me1, H3K4me3 and H3K27ac, was consistent with the histone modification assay showing a significant increase in H3K4me3 and H3K27ac peaks at promoter regions, both marks of active transcription. In contrast, RNA sequencing demonstrates a coordinated reduction in gene expression in a number of cell pathways including PI3K-AKT signalling, transcriptional misregulation in cancer and JAK-STAT signalling in spite of these histone changes. This highlights the complex mechanisms of transcriptional control within the cells which was reflected in analysis of the histone landscape in patient samples following ruxolitinib treatment.